2017
DOI: 10.33549/physiolres.933256
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Skeletal Muscle Hypertrophy in Wistar Rats to Different Resistance Exercise Models

Abstract: This study aimed to compare the effects of three different resistance exercise models on the quadriceps muscle crosssectional area, as well as on mTOR phosphorylation and other pivotal molecules involved in the upstream regulation of mTOR.Twenty-four male Wistar rats were divided into untrained (control), endurance resistance training, strength resistance training, and hypertrophy resistance training (HRT) groups (n=6). After 12 weeks of training, the red portion of the quadriceps was removed for histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…The muscles included in the selected articles were quadriceps femoris (Luciano et al, 2017; Neves et al, 2019), soleus (Cassilhas et al., 2013; Deschenes et al., 1994, 2000, 2015; Grans et al., 2014; Krause Neto & Gama, 2017; Padilha et al, 2017; Padilha et al., 2019; Prestes et al, 2012; Ribeiro et al, 2017; Shamsi et al, 2013), tibialis anterior [TA] (Jung et al., 2015; Lee et al, 2016; Neves et al, 2019; Prestes et al, 2012), gastrocnemius (Cassilhas et al., 2013; Grans et al., 2014; Lee et al, 2016; Ribeiro et al, 2017; Souza et al., 2014; Tibana et al, 2017), plantaris (Cassilhas et al., 2013; Deschenes et al., 2015; Mônico‐Neto et al, 2015; Padilha et al., 2019), FHL (Chi, Hou, Wu, Wang, & Yu, 2020; Gil & Kim, 2015; Hornberger & Farrar, 2004; Lee et al, 2016, 2018; Lee & Farrar, 2003; Padilha et al., 2019; Shamsi et al, 2014), extensor digitorum longus [EDL] (Deschenes et al., 1994; Krause Neto & Gama, 2017; Lim et al, 2018), flexor digitorum profundus [FDP] (Chi et al., 2020; Kwon et al, 2018), flexor digitorum longus [FDL] (Cassilhas et al., 2013), tríceps brachialis (Nascimento et al., 2013) and bíceps brachialis (Souza et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The muscles included in the selected articles were quadriceps femoris (Luciano et al, 2017; Neves et al, 2019), soleus (Cassilhas et al., 2013; Deschenes et al., 1994, 2000, 2015; Grans et al., 2014; Krause Neto & Gama, 2017; Padilha et al, 2017; Padilha et al., 2019; Prestes et al, 2012; Ribeiro et al, 2017; Shamsi et al, 2013), tibialis anterior [TA] (Jung et al., 2015; Lee et al, 2016; Neves et al, 2019; Prestes et al, 2012), gastrocnemius (Cassilhas et al., 2013; Grans et al., 2014; Lee et al, 2016; Ribeiro et al, 2017; Souza et al., 2014; Tibana et al, 2017), plantaris (Cassilhas et al., 2013; Deschenes et al., 2015; Mônico‐Neto et al, 2015; Padilha et al., 2019), FHL (Chi, Hou, Wu, Wang, & Yu, 2020; Gil & Kim, 2015; Hornberger & Farrar, 2004; Lee et al, 2016, 2018; Lee & Farrar, 2003; Padilha et al., 2019; Shamsi et al, 2014), extensor digitorum longus [EDL] (Deschenes et al., 1994; Krause Neto & Gama, 2017; Lim et al, 2018), flexor digitorum profundus [FDP] (Chi et al., 2020; Kwon et al, 2018), flexor digitorum longus [FDL] (Cassilhas et al., 2013), tríceps brachialis (Nascimento et al., 2013) and bíceps brachialis (Souza et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…According to Tibana et al (2017), despite no increased muscle mass, LRT is efficient in inducing a significant increase in the mean muscle fibers cross‐sectional area (fCSA) and the capacity of the rodent to carry the load. Yet, other studies corroborate these conclusions, demonstrating that LRT might stimulate hypertrophy of several different types of muscles (Jung et al., 2015; Know, Jang, Cho, Jang, & Lee, 2017; Lim, Gil, Quan, Viet, & Kim, 2018; Luciano et al, 2017; Ribeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Few studies have examined the effects of exercise on Sestrin levels. Luciano and colleagues reported that 12 weeks of resistance training increased Sesn2 protein content in the quadriceps of normal rats (Luciano et al, 2017). Regular exercise increased Sesn2 and Sesn3 expression in lean and obese mice (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training promotes micro-injuries in skeletal muscle, with alterations in the cytoskeleton, loss of sarcomeres and structural proteins, and necrosis of muscle fibers, among others (Damas et al, 2018). These changes may be caused by the mechanical stress induced by the training or activation of the calcium degradation pathway and the inflammatory response (Brook et al, 2016;Luciano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%